(untitled) (Physical Education, Health and Social Sciences, 2025)
The main objective of the study is to explore the acceptability and resistance to feminization in science, technology, engineering, and mathematics (STEM) fields at higher education levels. The number of females was lower in the STEM field. However, with time, females started taking an interest in science and technology subjects. As traditional gender roles are deeply rooted, STEM fields are still seen as a male domain in some countries. It is based on an exploratory qualitative research design grounded in an extensive review of research published documents on the topic of feminization in STEM education, acceptance, and resistance. A total of 82 research documents have been systematically extracted from well-reputed digital databases through the academic library, and the selection process has been continued until data saturation. Further, the thematic analysis technique has been employed to analyze the data qualitatively. The study findings reveal that momentous paces have been made in motivating and encouraging female participation in STEM fields, specifically in higher education. Precisely, higher education has been deeply embedded and interlinked with socio-cultural norms, gendered expectations, and institutional and structural barriers. Multiple factors often impede the inspiration, performance, career motivations, academic self-confidence, and job placement of female students in STEM fields.